Alpiniae oxyphylla fructus extract promotes longevity and stress resistance of C. elegans via DAF-16 and SKN-1 - Xiao, Man; Chen, Bocen; Niu, Kun; Long, Ziyu; Yang, Fan; Xie, Yiqiang (Frontiers in Pharmacology, 2022)
Background: Alpiniae Oxyphylla Fructus (AOF) is Traditional Chinese medicine and a dietary supplements for centuries, which posseses cardiotonic, neuroprotective, antioxidant, warming the kidney and nourish the spleen , these biological fuction is related to potential anti- aging properties. However, little is known about their effects on aging. This work aimed to investigate the effects of extracts of AOF on longevity and stress resistance in Caenorhabditis elegans( C. elegans) and the mechanisms that underlie its effects. Methods: Wild-type(WT) strand of C.elegans (N2 )worms were cultured in growth medium with or without AOF. First, we examined the effects of AOF on lifespan, reproduction and healthspan assay, stress resistance and oxidative analysis, lipofuscin levels . Second, The levels of ROS and MDA, the antioxidant enzyme activities were examined to explore the underlying mechanism of AOF. Finally, the expression of the longevity-related genes were investigated to further understand the AOF's underlying mechanism. Results: The lifespan of C. elegans was prolonged by 23.44% after treatment with high-dose AOF (100 ug/ml). AOF alleviated aging-related declines in C. elegans health and enhanced resistance to heat shock. Furthermore, AOF decreased reactive oxygen species and malondialdehyde, increased the activities of superoxide dismutase and catalase, and reduced accumulation of fat. AOF upregulated the expression of sod-3, gst-4, daf-16, and skn-1 but downregulated the expression of daf-2 and age-1 and accelerated the translocation of DAF-16 into the nucleus. The extended lifespan induced by AOF was reversed in daf-16(mu86) and skn-1(zu135) mutants, indicating that this gene is involved in AOF-regulated longevity. Conclusion: Our findings demonstrated that AOF extends lifespan and healthspan and enhances stress via boosting the activity of the antioxidant enzyme and controlling the expression of genes associated with insulin/IGF signaling and SKN-1 pathways. As a result, this work suggested AOF as a possible candidate to reduce the signs of aging by activating and inhibiting target genes.